A Comparative Economic Analysis of Different Reproductive Management Strategies in Two Dairy Sheep Farms in Greece - Dimitra V. Liagka; Antonis P. Politis; Maria Spilioti; Eleftherios Nellas; Panagiotis Simitzis; Konstantinos Tsiboukas (Agriculture)
The aim of this study was the economic comparison of two equivalent sheep farms with different reproductive management systems. Financial data were selected from a farm that applied artificial insemination (AI) and from one that applied natural mating (NM). The main objective of the analysis was to estimate the cost of each farm’s products and then to calculate their economic indicators. The AI farm had higher production costs, as a result of higher labor and fixed capital costs. On the other hand, the invested capital for the equipment and buildings of the NM farm was lower. Furthermore, the invested livestock capital based on the genetic value of the animals was higher in the AI farm. The AI farm produced milk, replacement ewe lambs and replacement ram lambs as its primary products, whereas the NM farm produced only milk as its primary product. The production costs for milk were 0.08 EUR/kg lower in the AI farm compared with the NM farm. The AI farm had a higher gross revenue and net and gross profit, resulting from the higher genetic value of the AI farm’s livestock. As indicated, the breeding and sale of genetically improved animals can increase the financial results of a farm and offer alternative sources of income. In conclusion, AI results in more sustainable and economically efficient sheep farming. In this regard, training for farmers and governmental economic support could promote AI application. Finally, the fortification of farmer group initiatives that facilitate the trade of dairy sheep products can accelerate AI utilization in dairy sheep farms in Greece.